Neuroblastoma with symptomatic epidural compression in the infant: The AIEOP experience. Issue 8 (12th March 2014) - De Bernardi, Bruno; Quaglietta, Lucia; Haupt, Riccardo; Castellano, Aurora; Tirtei, Elisa; Luksch, Roberto; Mastrangelo, Stefano; Viscardi, Elisabetta; Indolfi, Paolo; Cellini, Monica; Tamburini, Angela; Erminio, Giovanni; et al.
<x xml:space="preserve">Abstract</x> Background Symptoms of epidural compression (SEC) in children with neuroblastoma (particularly infants) may be misinterpreted, leading to delay in diagnosis. Patients and Methods Clinical, imaging and follow‐up data of 34 infants with neuroblastoma and SEC diagnosed between 2000 and 2011 at Italian AIEOP centers were retrieved and reviewed. Results Median age at initial SEC was 104 days (IQR 47–234). Main symptoms included motor deficit (85.3%), pain (38.2%), bladder and bowel dysfunctions (20.6% each). In the symptom‐diagnosis interval (S‐DI) (median, 12 days; IQR 7–34), the frequency of grade 3 motor deficit increased from 11.8% to 44.1% and that of bladder dysfunction from 20.6% to 32.4%. S‐DI was significantly longer (P = 0.011) for patients developing grade 3 motor deficit. First treatment of SEC was neurosurgery in 14 patients, and chemotherapy in 20. SEC regressed in 11 patients (32.3%), improved in 9 (26.5%), and remained stable in 14 (41.2%), without treatment‐related differences. Median follow‐up was 82 months. At last visit, 11 patients (32.3%) were sequelae‐free while 23 (67.7%) had sequelae, including motor deficit (55.9%), bladder (50.0%) and bowel dysfunctions (28.4%), and spinal abnormalities (38.2%). Sequelae were rated severe in 50% of patients. Severe sequelae scores were more frequent in patients presenting with spinal canal invasion >66% (P = 0.039) and grade 3 motor deficit (P = 0.084). Conclusions Both neurosurgery and chemotherapy provide unsatisfactory results once paraplegia has been established. Sequelae developed in the majority of study patients and were severe in a half of them. Greater awareness by parents and physicians regarding SEC is warranted. Pediatr Blood Cancer 2014; 61:1369–1375. © 2014 Wiley Periodicals, Inc.